WEBINARS AS A MEANS TO PROFESSIONAL DEVELOPMENT OF TEACHERS - Nataliia V. Morze; Artur B. Kocharian; Liliia O. Varchenko-Trotsenko (Information technologies and learning tools, 2014)
The article describes the possibilities of using webinar-oriented platforms as a means of professional development of teachers and gives examples of using the webinars based on Lync 2013. There is studied the educational component of webinars, namely – interactive method. The authors considered advantages and prospects of using webinars in the implementation of the distance form of researchers and teachers training in higher education and worked out for them guidelines for organizing and conducting webinars.